PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMP NEGERI 1 NGARINGAN - Hidayat, Muhammad Taufiq Zakki; Mangiri, Herry S; Damar Rani, Handini Arga (Joined Journal (Journal of Informatics Education), 2020)
The purpose of this study is 1). Generate a Library Information System application according to needs that include book inventory data, journal data on borrowing and repayment, search data for book collections, and library membership data at SMP Negeri 1 Ngaringan; 2). Development of desktop web-based library information systems as a reference for decision making and education unit policies in evaluating the performance of school principals. As well as information services for the academic community of SMP Negeri 1 Ngaringan; 3). As one of the requirements for obtaining a Bachelor's degree, in the Undergraduate Study Program of Informatics Education at the Faculty of Science at Ivet University.                 This research is a Research and Development research in the form of a web-based library information system application that is run locally. The development model used is a waterfall which includes, needs analysis, design, implementation and final testing. At the design stage of this study using the Unified Modeling Language (UML) model as a reference in the system being built. Whereas the testing phase of this information system focuses on aspects of functionality and usability.                 The results of the study were obtained as follows;(1) web-based library information system is developed with codeigniter and waterfall development models from the stages of analysis, design, implementation and testing. (2) the functionality aspect of each system runs with 100% success. While the results of testing conducted by this system are included in the category of "Very Strong / Very Worthy" with a value of 96.18% in the usability aspect. Keywords: Information System, Library, Website.